Calcineurin Inhibitor and Nonsteroidal Anti‐inflammatory Drug Interaction: Implications of Changes in Renal Function Associated With Concurrent Use. (25th May 2018) - Delzer, Luke M.; Golightly, Larry K.; Kiser, Tyree H.; Biggins, Scott W.; Lewis, Victor J.; Kim, Ike I.
Abstract: Evidence for a drug interaction between calcineurin inhibitors (CNIs) and nonsteroidal anti‐inflammatory drugs (NSAIDs) is meager, and the magnitude of risk for adverse renal effects associated with this interaction is unclear. To explicate these uncertainties, sequential measures of kidney function were evaluated in hospitalized adult solid organ or allogeneic hematopoietic stem cell transplant recipients who received maintenance CNI therapy and concurrent treatment with an oral or parenteral NSAID. A comparator group of closely matched transplant recipients on CNI therapy who did not receive NSAID treatment during hospitalization was similarly evaluated. Among inpatients on CNIs, treatment‐emergent acute kidney injury occurred in 5 of 41 (12.2%) patients exposed to concurrent NSAIDs and in 7 of 126 (5.6%) of matched patients who were not exposed to NSAIDs (relative risk ratio 2.20, 95% confidence interval 0.74 to 6.54). During hospitalization, an increase in serum creatinine above baseline occurred in 80.5% of patients on CNI therapy who were exposed to NSAIDs as compared with 56.3% of patients on CNIs who were not exposed ( P = .001). NSAID administration was an independent predictor for a rapid increase in serum creatinine ( P = .026). The event rate for worsened renal function was highest among patients exposed to parenteral ketorolac. Because the likelihood of developing treatment‐related worsening of renal function is increased with combined use of CNIs and NSAIDs, concurrent use of these medications is inadvisable. Patients and clinicians should be counseled accordingly.